(3cJGH aj GdWH GdYQHis
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd fhY GdEfSGf Cced GdCfhGY hHYO agPG eDda dWja (B( (3dGjgedg (B) (3GdEfSGf hdG jMJGL ai eYQaJg Edi YhGf GdHGH GdChd ai eYQaI CUhd GdCeQGV s
(3BNQgG (B:s
(3hTQH GdNeQ jhQK NddkG ai LhgQ GdYbd hjaSO GdOeGZ hjMOK GdfSjGf hGdUQY hjhLH SNW GdQH hjfSi GdTgGOI YfO GdehJ hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdWHs